PENGARUH KONDISI SOSIAL EKONOMI ORANG TUA TERHADAP MINAT SISWA MELANJUTKAN PENDIDIKAN KE PERGURUAN TINGGI PADA SISWA KELAS XI SMK TELKOM PEKANBARU - Yustina Juni purnama sari Sari; Suarman Suarman; RM Riadi (Jurnal Pendidikan Ekonomi (JURKAMI), 2023)
The quality of human resources should improve and become more competitive as education levels rise. A high level of education is essential to developing high-caliber labor. In contrast to other nations, Indonesia's participation rate for students who continue their education in tertiary institutions is still low. This research is motivated by the lack of interest of students to continue their education to tertiary institutions. This study aims to determine the effect of parents' socio-economic conditions on students' interest in continuing their education to tertiary education in class XI students of SMK Telkom Pekanbaru. This study uses a quantitative descriptive method. The population in this study were 206 students. The research sample used a simple random sampling technique of 67 students. This research data collection method using a questionnaire. The data analysis technique used is simple regression analysis. Based on the results of the study, it was shown that there was a positive and significant influence on the socio-economic conditions of parents on students' interest in continuing their education to tertiary institutions in class XI students of SMK Telkom Pekanbaru.